Omega-3 fatty acids mitigate histological changes and modulate the expression of ACACA, PFK1 and ET-1 genes in broiler chickens under environmental stress: a pulmonary artery, cardiomyocyte and liver study - Shahgol Rahbari; Seyed Davood Sharifi; Abdolreza Salehi; Sara Pahlavan; Shirin Honarbakhsh (Poultry Science)
ABSTRACT: The aim of this study was to investigate the effects of omega-3 fatty acids on blood biochemical parameters, histological changes in pulmonary artery, cardiomyocytes, and liver, as well as the expression of ACACA, PFK1, and ET-1 genes in broiler chickens under environmental stress (high stoking density). A total of 420 one-day-old male Ross broilers were used in a 2 × 2 factorial arrangements, with 2 levels of environmental stress (without and with stress; 9 and 17 birds/m2, respectively) and 2 levels of omega-3 fatty acids (low and high; 0.057 and 0.5% of the diet, respectively) in a completely randomized design comprising 4 treatments and 5 replicates per each. The body weight decreased at d 40 because of environmental stress (P ≤ 0.05). The ascites heart index (AHI) in broilers fed high omega-3 fatty acids diets was lower (P = 0.062) than broiler fed low omega-3 fatty acids diet (0.279 vs. 0.316). Stressed birds showed a higher neutrophil: lymphocyte ratio compared to non-stressed birds (P ≤ 0.05). Broiler chickens receiving high omega-3 fatty acids diets exhibited elevated levels of hematocrit (HCT), hemoglobin (HGB), and lymphocytes (P ≤ 0.05). The neutrophil: lymphocyte ratio, and serum concentration of alanine aminotransferase (ALT), and aspartate aminotransferase (AST) decreased in broilers fed high omega-3 fatty acids diets (P ≤ 0.05). In stressed broilers on a high omega-3 diet, pulmonary artery wall thickness decreased (P ≤ 0.05). Additionally, under stress, myocardial cell diameter, hepatocyte and cell nucleus diameter significantly increased (P ≤ 0.05). Stressed broilers showed an increased relative fold change in PFK1 enzyme activity but reduced ET-1 mRNA expression in the liver compared to stressed birds on a high omega-3 diet (P ≤0.05). In conclusion, the results indicate that dietary omega-3 fatty acids have the potential to alleviate the adverse histological changes in the pulmonary artery, cardiomyocytes, and liver, while also modulating the expression of genes ACACA, PFK1, and ET-1 that are influenced by environmental stress in broiler chickens.